Dinamika Keluarga dalam Pembentukan Identitas Diri Tokoh Alie Pada Novel Rumah Untuk Alie - Danica, Wahyu Nova; Sutopo, Bakti; Widoyoko, Riza Dwi Tyas (STKIP PGRI Ponorogo Press, 2025)
he family is the first environment that influences the formation of an individual's identity. When the family fails to fulfill its roles and functions, it risks causing an identity crisis in the individual. This study examines the dynamics of a dysfunctional family in Lenn Liu's novel Rumah untuk Alie and its influence on the formation of the character Alie's identity. The study aims to describe the aspects of family dynamics experienced by the character Alie and analyze their influence on the psychological aspects of the main character's identity formation process. The method used is descriptive qualitative with a literary psychology approach and Murray Bowen's family systems theory. Data in the form of text excerpts are analyzed using content analysis techniques. The results of the study show that the character Alie experiences emotional, psychological, and social dynamics that create emotional disconnection and psychological wounds. Alie's inability to differentiate herself and her tendency toward emotional cutoff caused her identity to form in a fragile state. This study also shows that family dynamics have a significant influence on an individual's psychological aspects. This is evidenced by the emergence of internal conflicts, feelings of insecurity, and confusion in social roles experienced by the character Alie, thereby affecting her emotional stability and decision-making in her life.